Assistance Program on Training, Body Composition, and VO₂Max Assessment for Recreational Runners - Arfin Deri Listiandi; Neva Widanita; Dewi Anggraeni; Iqbal Indra Awaludin (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aimed to improve the knowledge and ability of recreational runners in implementing structured training programs to enhance running performance and cardiorespiratory fitness. The program was conducted in September 2025 in Purwokerto, involving 38 members of a recreational running community. The method consisted of exercise education, three sessions of speed training assistance, and body composition as well as Balke test assessments to measure VO₂Max. The results indicated an increase in participants’ knowledge about training principles that improve running performance. Body composition assessment showed that most participants were in the normal category (57.9%), while the VO₂Max test revealed that the majority were in the moderate category (42.1%). This activity demonstrates that an educational and scientific approach combined with fitness assessment can effectively enhance runners’ awareness in applying structured and measurable training.